FAKTOR YANG MEMPENGARUHI PASIEN TUBERKULOSIS RESISTAN OBAT YANG TIDAK MEMULAI PENGOBATAN: LITERATURE REVIEW - Indri Rizkiyani; Syahrizal Syarif (J-KESMAS: Jurnal Kesehatan Masyarakat, 2024)
Drug-resistant tuberculosis (DR TB) patients who have been diagnosed but not enrolled to treatment could be a source of primary transmission and the risk of increasing DR TB cases in the community. The aim of this literature review is to determine the factors that influence pre-treatment lost to follow up of DR TB patients by searching the literature through Google Scholar, ScienceDirect, ProQuest and PubMed which was published in the period 2016 to 2023 with the keywords "drug resistant tuberculosis", "treatment initiation", “enrollment rate”, and “pre-treatment lost to follow up”. Seven articles were obtained of which three research articles came from China, two from South Africa, one from India, and one from Ethiopia. Factors that influence DR TB patients not starting treatment include age, economic status, drug sensitive TB treatment status, inadequate health service infrastructure, lack of experienced clinicians, health seeking behavior, and health system delays. The low rate of DR TB treatment initiation requires special attention, both in terms of health services provided by the government and support from the community, in order to break the chain of transmission in the community.